Загальноправові завдання і основні напрями забезпечення громадської безпеки в Україні - Панова, О. О.; Panova, O. O.; ORCID: http://orcid.org/0000-0002-3533-5076 (Право і безпека. - 2014. - № 3 (54). - С. 142-145, 2014)
На підставі аналізу наукових точок зору та відповідних нормативно-правових актів подано авторське бачення напрямів забезпечення громадської безпеки в Україні. Встановлено, що напрями забезпечення громадської безпеки розглядаються крізь призму сфер суспільних ві- дносин, а саме: у політичній сфері, в економічній сфері, у соціальній сфері, у воєнній сфері.

Analysis of scientific papers in regard to the goals, objectives and main directions of guaranteeing public safety is realized. Priority functions, i.e. the main activities of public security subjects in modern conditions of Ukraine are found out. It is determined that the analysis of complex target programs guaranteeing public safety shows that they formulate the goals, terms and stages of program realization; the source of funding, expected outcomes of the program are stated; the system of control over program realization is determined. The program contains the content of the problem and the rationale for its solution with the help of programmed methods, the system of programmed measures, etc. is provided It is grounded that the improvement of legal regulation of relations in the field of public safety is aimed at creation of high qualified regulatory and legal basis guaranteeing the effective functioning of the system of public safety protection if there is the state and public control over its subjects’ activity. It is established that the main directions of public security subjects’ activity in modern conditions in Ukraine are strengthening cooperation and coordination of all public safety subjects, organization of effective management by operational forces belonging to different safety subjects in emergencies and other circumstances requiring immediate intervention by interagency security forces.

На основании анализа научных точек зрения и соответствующих нормативно-правовых актов представлено авторское видение направлений обеспечения общественной безопасности в Украине. Установлено, что направления обеспечения общественной безопасности рассматриваются сквозь призму сфер общественных отношений, а именно: в политической сфере, в экономической сфере, в социальной сфере, в военной сфере.
General and legal tasks and the main directions of keeping public safety in Ukraine
Общеправовые задачи и основные направления обеспечения общественной безопасности в Украине
Панова, О. О. Загальноправові завдання і основні напрями забезпечення громадської безпеки в Україні / О. О. Панова // Право і Безпека. - 2014. - № 3. - С. 142-145.
Панова О. О. "Загальноправові завдання і основні напрями забезпечення громадської безпеки в Україні." Право і Безпека 3 (2014): 142-145.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; громадська безпека; общественная безопасность; забезпечення громадської безпеки; обеспечение общественной безопасности; public peace; public order